Development of Electronic Handouts Using Numerical Literacy-Based Mathemagics Methods for Learning in the Digital Era - Meria Ultra Gusteti; Suci Wulandari; Widdya Rahmalina; Melani Putri; Elva Kurnia Putri (JURNAL EKSAKTA PENDIDIKAN (JEP), 2023)
This research is motivated and conducted to address the problem of low numeracy literacy among students and the limited electronic-based learning media with game-based methods. The urgency of this research is crucial because low numeracy literacy can affect students' ability to solve mathematical problems in their daily lives and the future. The lack of engaging learning media can also affect students' interest in learning. Therefore, this study aims to develop an electronic Mathemagic handout based on numeracy literacy. The development model used in this research is the DDD-E model. The developed handout product has been validated twice by material and media validators. After revising it based on their suggestions and inputs, the average validation score obtained is 87.1%. These results indicate that the developed electronic Mathemagic handout based on numeracy literacy meets the perfect validation criteria. The solution offered by this research is to develop an engaging mathematical learning media using game-based methods to improve students' numeracy literacy. It is hoped that the electronic Mathemagic handout based on numeracy literacy can help increase students' interest and learning ability in mathematics. As a result, students can be more confident and have sufficient ability to solve mathematical problems in their daily lives and the future. The study implies that educators and policymakers can consider implementing the electronic Mathemagic handout in their teaching methods to enhance students' numeracy, literacy, and interest in mathematics. Additionally, the study underscores the importance of using innovative and engaging approaches in teaching to foster a love for learning and improve academic outcomes.